Stage-dependent prognostic shift in mismatch repair-deficient tumors: Assessing patient outcomes in stage II and III colon cancer - Hestetun, Kjersti Elvestad; Rosenlund, Nina Benedikte; Stanisavljević, Luka; Dahl, Olav; Myklebust, Mette Pernille (Frontiers in Oncology, 2022)
Introduction Deficient mismatch repair (dMMR) or high microsatellite instability (MSI-H) is associated with an improved prognosis in colon cancer stage II but poor prognosis in stage IV colon cancer. The clinical significance of dMMR in colon cancer stage III is not established. Methods Tissue microarrays (TMAs) from 544 patients with colon cancer stage II and III with clinicopathological and survival data were stained for mismatch repair (MMR) proteins, CD3, CD8, and programmed death ligand-1 (PD-L1), and programmed death ligand- 1 (PD-L1). Patient outcomes were reviewed. Results In stage III colon cancer, dMMR was a marker of poor disease-free survival (DFS) (Kaplan–Meier, mean survival in months: dMMR: 28.76 (95% CI 18.46–39.05) vs. pMMR 40.91 (37.20–44.63), p=0.014, multivariate Cox regression: hazard ratio (HR) 4.17 (95% CI 2.02–8.61), p<0.001). In stage II colon cancer, there was a tendency toward improved DFS for dMMR patients (dMMR: 57.14 (95% CI 54.66–59.62) vs. pMMR 53.54 (95% CI 51.48–55.60), p=0.015, multivariate Cox regression HR 0.24 (95% CI 0.06-1.04), p=0.057). CD3, CD8, and PD-L1 expression was not associated with prognosis of dMMR patients. Multivariate Cox regression analysis showed a significant interaction between the MMR phenotype and stage (p=0.001). Conclusion dMMR is associated with an improved prognosis in stage II colon cancer but is no longer associated with a favorable prognosis in stage III colon cancer.